1994
DOI: 10.1080/13510002.1994.11746959
|View full text |Cite
|
Sign up to set email alerts
|

Steady magnetic fields effect on lipid peroxidation kinetics

Abstract: The effect of steady magnetic fields (ranging from 0 to 280 mT) has been investigated on the kinetics of non-enzymatic lipid peroxidation occurring in a model system consisting of liposomes obtained from 1, 2-dioleoylphosphatidylcholine by oxygen consumption. The process was found to be accelerated by weak steady magnetic fields. A computer simulation method was employed to detect the reactions that govern the process kinetics, to elucidate magneto-sensitive stages (initiation and reduction of iron(III), as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Studies showed that exposure to ELF-MF caused increased lipid peroxidation [13,14]. Fiorani et al [15] suggested that 50 Hz 0.5 mT magnetic field increased the damage in an oxidatively stressed erythrocyte system.…”
Section: Introductionmentioning
confidence: 98%
“…Studies showed that exposure to ELF-MF caused increased lipid peroxidation [13,14]. Fiorani et al [15] suggested that 50 Hz 0.5 mT magnetic field increased the damage in an oxidatively stressed erythrocyte system.…”
Section: Introductionmentioning
confidence: 98%
“…Aristarkhov et al (1983) demonstrated an increase of lipid peroxidation level in liposomes (1,2-dioleophosphatidylcholine) exposed to SMF (8 mT). SMF, under in vitro chemical stimulation, can influence lipid peroxidation kinetics in liposomes and enhance the production of oxygen free radicals in human red blood cells (Lalo et al 1994;Chignell and Sik 1998). Previous studies by Amara et al (2006Amara et al ( , 2007Amara et al ( , 2009) showed an increase in MDA level in male rat testis, hippocampus, liver and kidney after exposure to SMF (128 mT, 1 h/day during 30 consecutive days).…”
Section: Resultsmentioning
confidence: 99%
“…Increased lipid peroxidation was observed for steady MF of flux density of ca. 8 mT [18]. Artificial phospholipid membranes were used in this test.…”
Section: Discussionmentioning
confidence: 99%